2016
DOI: 10.1002/jcb.25626
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐TAK1 (MAP3K7) Induces Adipocyte Differentiation Through PPARγ Signaling

Abstract: BMPs have been shown to promote adipocyte differentiation through SMAD-dependent signaling. However, the role of TGF-β-activated kinase 1 (TAK1) in non-canonical BMP signaling in adipocyte differentiation remains unclear. Here, we show that TAK1 inhibition decreases lipid accumulation in C3H10T1/2 mesenchymal stem cells (MSCs) induced to differentiate into adipocytes. TAK1 knockdown by siRNA further confirms that TAK1 is required for adipocyte commitment of MSCs. Additionally, TAK1 knockdown inhibits adipogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Both in vivo and in vitro, it was confirmed that Tak1 deprivation leads to strong inhibition of the proliferative activity of BMMSCs without affecting their differentiation potential. Notably, 5zox treatment during differentiation suppressed chondrogenesis and osteogenesis, which was consistent with previous results observed in Tak1-suppressed cells [11,12,26,27]. In the in vivo experiment, we observed that 5zox treatment blocked expansion of BMMSCs and induced growth retardation; however, both the number of BMMSCs and total body weights recovered to normal levels upon discontinuing the 5zox treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Both in vivo and in vitro, it was confirmed that Tak1 deprivation leads to strong inhibition of the proliferative activity of BMMSCs without affecting their differentiation potential. Notably, 5zox treatment during differentiation suppressed chondrogenesis and osteogenesis, which was consistent with previous results observed in Tak1-suppressed cells [11,12,26,27]. In the in vivo experiment, we observed that 5zox treatment blocked expansion of BMMSCs and induced growth retardation; however, both the number of BMMSCs and total body weights recovered to normal levels upon discontinuing the 5zox treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, histological staining of the retrieved samples showed that formation of bone matrix, lipid droplets and cartilage matrix was significantly impaired by NICD, which may indicate that NICD not only inhibits osteogenic differentiation but also suppresses adipogenic and chondrogenic differentiation of MSCs [ 19 , 49 , 50 ]. This result indicated that nonclassical BMP signaling is required for commitment of C3H10T1/2 pluripotent stem cells toward the adipocyte lineage [ 51 , 52 ]. According to previous studies, the Notch pathway has a crucial function in cell cycle regulation [ 53 , 54 ], and our results also demonstrate that Notch signaling has the ability to promote cell proliferation and maintain the self-renewal capacity of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The reactive oxygen species (ROS)-thioredoxin interacting protein (TXNIP) pathway mediates hepatocellular NOD-like receptor (NLR) family pyrin domain containing 3 (NLRP3) inflammasome activation, inflammation and lipid accumulation in fructose-induced NAFLD [34]. Mitogen-activated protein kinase kinase kinase 7 (MAP3K7) induced adipocyte differentiation through peroxisome proliferator-activated receptor gamma (PPARγ) signaling [35].…”
Section: Knockdown Of Arrdc3 Inhibits Inflammasome-associated Gene Exmentioning
confidence: 99%
“…We also observed that knockdown of ARRDC3 in human hepatocytes down-regulates inflammasome-associated gene expression (Table 1). It has been reported that activation of inflammasomes plays a role in the development of NAFLD and NASH [27][28][29][30][31][32][33][34][35][36][37][38][39][40]44]. The association between ARRDC3 and inflammasome-related pathways may have a role in the development of NAFLD and NASH.…”
Section: Knockdown Of Arrdc3 Inhibits Inflammasome-associated Gene Exmentioning
confidence: 99%